PENGEMBANGAN ASPEK PEMASARAN USAHA KOPI BU TIANI DI DESA SUMBERMANJING WETAN - Novi Puji Lestari; Fika Fitriasari; Mochamad Rofik (Studi Kasus Inovasi Ekonomi, 2021)
The purpose of this service is to increase the added value of Argotirto coffee in the Sumbermanjing Wetan sub-district, Malang Regency. After going through several phases, this empowerment finally resulted in the ground coffee brand "Argotirto," which is a premium robusta ground coffee with the quality of selected coffee beans. The post-harvest process makes the potential profits of partner farmers to increase by at least 25% -40%.